Leucas angularis Benth. (Lamiaceae): New record to the flora of Maharashtra, India - Balasaheb Shantilal Kale,; Sanjay Appaji Khairnar,; Suresh Ganpat Sabale,; Sachin Vasantgir Gosavi,; Mangesh Balasaheb Avhad, (The Bioscan, 2024)
The current research article deals with the new plant species addition to the floristic study of Maharashtra state, India alongside the definite depiction, morphology, and vegetation. During the broad botanical investigation of the northern Western Ghats of Maharashtra, Leucas angularis Benth. (Lamiaceae) are gathered. After macroscopic and microscopic perception and a basic survey of the accessible references, these species are found as new records of the flora of Maharashtra, India. Leucas angularis Benth. a new addition of the Flora of Maharashtra, India.